2017
DOI: 10.1111/bjd.15305
|View full text |Cite
|
Sign up to set email alerts
|

Determinants for drug survival of methotrexate in patients with psoriasis, split according to different reasons for discontinuation: results of the prospective MTX-CAPTURE

Abstract: Drug survival of MTX was low with 15% of patients 'on drug' after 5 years. Side-effects alone or in combination with inadequate disease control were more important in the context of treatment discontinuation than inadequate disease control alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
33
3
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(47 citation statements)
references
References 15 publications
8
33
3
3
Order By: Relevance
“…Patients on both oral and subcutaneous methotrexate were included. The median drug survival was 1·8 years and 15% of patients remained on methotrexate after 5 years . This is similar to the previously published studies on this subject .…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Patients on both oral and subcutaneous methotrexate were included. The median drug survival was 1·8 years and 15% of patients remained on methotrexate after 5 years . This is similar to the previously published studies on this subject .…”
supporting
confidence: 88%
“…Methotrexate is the recommended first‐line systemic therapy for moderate‐to‐severe psoriasis . This issue of the BJD includes the paper by Otero et al ., one of the few well‐designed prospective studies to assess drug survival with methotrexate in patients with psoriasis without psoriatic arthritis . Patients on both oral and subcutaneous methotrexate were included.…”
mentioning
confidence: 99%
“…This is due to its well‐established efficacy, safety profile and low cost . Across published data, MTX demonstrates rates of ≥ 75% improvement in Psoriasis Area and Severity Index (PASI 75) of approximately 40% at weeks 12–16, with a median drug survival of 1·8 years . The cost of oral MTX is less than 1%, and subcutaneous (SC) MTX less than 10% of that of the cheapest biologic agent in the Republic of Ireland.…”
mentioning
confidence: 99%
“…The cost of oral MTX is less than 1%, and subcutaneous (SC) MTX less than 10% of that of the cheapest biologic agent in the Republic of Ireland. Oral MTX may be limited by its toxicity and drug survival …”
mentioning
confidence: 99%
“…In addition, methotrexate is the recommended first-line systemic treatment for moderate to severe plaque psoriasis patients in accordance with guidelines from the United Kingdom, United States, and Europe (Menter et al, 2009). Although it is efficient (Otero et al, 2017;Raaby et al, 2017), methotrexate has been reported to have hepatotoxicity (Maybury et al, 2014). We found that methotrexate significantly inhibited the viability of resting/LPS-stimulated macrophages (see Supplementary Figure S2a and b) and primary hepatocytes (Supplementary Figure S2c).…”
Section: Cis-khellactone Inhibited the Classical Activation Phenotypementioning
confidence: 72%